2014
DOI: 10.1186/s13054-014-0515-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of red blood cell transfusion and in-hospital mortality in patients admitted to the intensive care unit: a systematic review and meta-analysis

Abstract: IntroductionPrevious research has debated whether red blood cell (RBC) transfusion is associated with decreased or increased mortality in patients admitted to the intensive care unit (ICU). We conducted a systematic review and meta-analysis to assess the relationship of RBC transfusion with in-hospital mortality in ICU patients.MethodsWe carried out a literature search on Medline (1950 through May 2013), Web of Science (1986 through May 2013) and Embase (1980 through May 2013). We included all prospective and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Because OR and HR were used inconsistently in the various analyses, the term “risk” may refer to OR or HR 41 . Previous meta-analyses in the literature also considered HR and OR as RR 42,43 . Another potential limitation of this study is that it cannot account for the ‘healthy user’ effect in the individual studies, since elderly usually suffer from various chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Because OR and HR were used inconsistently in the various analyses, the term “risk” may refer to OR or HR 41 . Previous meta-analyses in the literature also considered HR and OR as RR 42,43 . Another potential limitation of this study is that it cannot account for the ‘healthy user’ effect in the individual studies, since elderly usually suffer from various chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the widespread use of blood transfusions in patients with anemia, several studies have failed to demonstrate a benefit and, in fact, blood transfusions have shown to be harmful in many clinical settings. 1418 Some suggest that it is not the practice of treatment of anemia with blood transfusions that is associated with adverse events, but rather the anemia itself that increases the patients’ risk of postoperative complications. 4 Interestingly, few reports have evaluated the combined effect of preoperative anemia and blood transfusions, although this is a relevant clinical question for physicians.…”
Section: Introductionmentioning
confidence: 99%
“…A causal link between transfusion and mortality is difficult to determine since mortality may be associated with the underlying disease or transfusion itself. A systematic study to assess the association of red blood cell transfusion and in-hospital mortality in patients admitted to the ICU failed to identify association across studies for the number of blood units transfused [ 23 ]. Also, a meta-analysis on whole blood transfusion was not associated with in-hospital/30-day mortality in patients treated for traumatic haemorrhagic shock [ 24 ].…”
Section: Discussionmentioning
confidence: 99%